Inguinoscrotal lymphangioma mimicking hydrocele: a case report - Yadav, Sudha; Rattan, Kamal Nain; Yadav, Pawan; Gavhane, Sunil (International Journal of Contemporary Pediatrics, 2018)
Scrotal lymphangiomas are hamartomata’s lymphatic malformations with no risk of malignant transformation, resulting due to inadequate drainage of lymph from sequestered lymph or lack of continuation between lymphatics and venous channels. Here we report a case of scrotal lymphangioma in a 1.5 years old child who presented with scrotal swelling and misdiagnosed as hydrocele. Child was managed successfully with surgical resection of the mass and doing well now.